2007
DOI: 10.1186/1471-2164-8-95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toxicity of the mycotoxin citrinin using yeast ORF DNA microarray and Oligo DNA microarray

Abstract: Background: Mycotoxins are fungal secondary metabolites commonly present in feed and food, and are widely regarded as hazardous contaminants. Citrinin, one of the very well known mycotoxins that was first isolated from Penicillium citrinum, is produced by more than 10 kinds of fungi, and is possibly spread all over the world. However, the information on the action mechanism of the toxin is limited. Thus, we investigated the citrinin-induced genomic response for evaluating its toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 23 publications
5
64
1
Order By: Relevance
“…Mutants with two or more gene deletions that disrupt the pleiotropic drug resistance 5 (PDR5) gene, which encodes a multidrug resistance protein, have lead to increases in mycotoxin susceptibility (McCormick et al, 1999, Mitterbauer et al, 2003, indicating that other stress response genes might also influence mycotoxin resistance in yeast. Recently, studies on mycotoxin-yeast interactions have revealed that metabolism and stress response genes are induced under patulin (Iwahashi et al, 2006) and citrinin (Iwahashi et al, 2007) exposure. Aflatoxin B1 is also reportedly degraded by yeast (El-Shiekh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutants with two or more gene deletions that disrupt the pleiotropic drug resistance 5 (PDR5) gene, which encodes a multidrug resistance protein, have lead to increases in mycotoxin susceptibility (McCormick et al, 1999, Mitterbauer et al, 2003, indicating that other stress response genes might also influence mycotoxin resistance in yeast. Recently, studies on mycotoxin-yeast interactions have revealed that metabolism and stress response genes are induced under patulin (Iwahashi et al, 2006) and citrinin (Iwahashi et al, 2007) exposure. Aflatoxin B1 is also reportedly degraded by yeast (El-Shiekh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The stress response gene mutants were used mainly because of the high induction of stress response-and metabolism-related genes, as well as because of the importance of these genes for multidrug resistance, as highlighted in earlier studies (Iwahashi 2006, Iwahashi 2007. To develop a simple yeast system that can evaluate mycotoxicity by analyzing such receptivity using a suitable set of mutant strains, we investigated the effects of mycotoxin exposure on various mutants harboring disrupted genes associated with stress responses and metabolism (including energy).…”
Section: Introductionmentioning
confidence: 99%
“…Controls (n = 100) were injected with 100 μl of PBS. After challenge, the clams were returned to the tanks and maintained at 15°C until sampling at 3,8,24, and 72 hours after challenge. The cumulative mortality rate at the end of the experiment, 72 hours, was 44%.…”
Section: Methodsmentioning
confidence: 99%
“…This platform has been used by scientists to study the expression profile in many species from yeast to human [24,25]. Microarrays have also been applied to bivalves for different purposes [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has applied microarrays to examine the molecular response of a yeast model using various toxic materials. As summarized in Table 2, we have detected differentially expressed genes and determined the mechanism against the toxic matter for each of terpinene (Parveen et al, 2004), dimethyl sulfoxide (Murata et al, 2003), mycotoxin citrinin (Iwahashi et al, 2007), thorium , cadmium (Momose and Iwahashi, 2001), and thiuram (Kitagawa et al, 2002).…”
Section: Evaluation For Toxicological Damagementioning
confidence: 99%